The prevalence of Internet addiction and its related factors among medical students of International Islamic University Malaysia (IIUM), Kuantan Campus - Swe, Swe Latt; Mohd Rus, Razman; Ab Rahman, Jamalludin; Nasreen, Hashima E; Abd. Aziz, Karimah Hanim; Pasi, Hafizah (Malaysian Public Health Physicians' Association, 2016)
Although the Internet is undeniably helpful in medical students’ life, they need to be aware of their level of internet usage and proper time management. This study measured the prevalence of Internet addiction (IA) and its related factors among year 1 to 5 medical students at International Islamic University Malaysia. A cross-sectional study was done at Faculty of Medicine, Kuantan Campus in August 2015 among 270 medical students using a self-administered online questionnaire (Internet Addiction Test-20) with quota sampling method. Chi-square test,‘t’ test and ‘U’ test were applied to infer an association between IA and factors related to using Internet. The prevalence of normal, mild and moderate internet user were 60.9% (n=164), 36.9% (n=100) and 2.2% (n=3) respectively. Internet addiction (mild and moderate) was higher among mean (SD) age of 22.7(1.9) years old, female (61%), Year 1(27%), living in dormitory (90%), using Smartphone (72%), using Internet for 7 years and more (48%), night user (63%) and spent 2 to 5 hours per day (40%) with fast speed Internet (52%). They used the Internet for communicating with friends and family (96%), searching scientific research (84%), checking emails (81%), reading news (76%), chatting with new people (73%), and downloading films and music (64%). However, these findings were not statistically significant. High prevalence of normal Internet user and no severe IA among medical students under study is a favorable condition to instill awareness on their level of Internet usage and students should manage their time wisely by participating in other activities.